APLIKASI TEKNOLOGI FERMENTASI DALAM PRODUKSI PUPUK ORGANIK UNTUK MENUNJANG PERTANIAN PADI LOKAL ORGANIK DI KECAMATAN PENEBEL, KABUPATEN TABANAN, PROPINSI BALI - Ratna Adi, I G.P.; Siti, N.W.; Sardiana, I K. (Buletin Udayana Mengabdi; Vol 16 No 1 (2017), 2018)
Community service activities aimed at transferring fermentation technology for the production of organic fertilizer in supporting the local Organic rice farming in Jatiluwih Village, Tabanan Subdistrict, Tabanan District. The methods applied in the community empowerment of KKN PPM activities are as follows: (1) Participatory coordination and communication with farmer groups (subak) organizing organic farmers to formulate programs ranging from planning, operation and evaluation; (2) Counseling to build community perceptions and understanding of innovations or programs implemented; (3) Training and simulation of applied ipeks transferred to the community; (4) Assistance is regular and ongoing meetings between assistants and target communities to transferred science and technology can be carried out independently by the community; The results show that the activities of science and technology dissemination through KKN PPM program in Jatiluwih Village, Kecamatan Police, Tabanan District can take place well indicated by active participation and high adoption of science and technology. The active participation of partners in all technological dissemination activities is quite high, at 77.5%. The ability of science and technology adoption of miitra to produce products independently is high enough, that is 80%.